2015
DOI: 10.1126/sciadv.1400177
|View full text |Cite
|
Sign up to set email alerts
|

The supramammillary nucleus and the claustrum activate the cortex during REM sleep

Abstract: Plasticity and cortical activation during REM sleep is shown by a subset of cortical and hippocampal neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
107
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 81 publications
(116 reference statements)
11
107
1
Order By: Relevance
“…This is important given the influence of the supramammillary nuclei on hippocampal theta frequency (e.g., Kirk, 1998). As such, many studies that have assessed the effects of mammillary body lesions, or inactivation, on hippocampal theta can be difficult to interpret when damage extends into the overlying supramammillary nuclei (Sharp and Koester, 2008;Zakowski et al, 2017) and vice versa (Renouard et al, 2015). Nevertheless, the only previous study that has examined hippocampal theta following mammillary body manipulation in non-anesthetized animals established a similar pattern of changes to those reported here, with a reduction in hippocampal theta-frequency (Sharp and Koester, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This is important given the influence of the supramammillary nuclei on hippocampal theta frequency (e.g., Kirk, 1998). As such, many studies that have assessed the effects of mammillary body lesions, or inactivation, on hippocampal theta can be difficult to interpret when damage extends into the overlying supramammillary nuclei (Sharp and Koester, 2008;Zakowski et al, 2017) and vice versa (Renouard et al, 2015). Nevertheless, the only previous study that has examined hippocampal theta following mammillary body manipulation in non-anesthetized animals established a similar pattern of changes to those reported here, with a reduction in hippocampal theta-frequency (Sharp and Koester, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…2). Unlike in the hippocampus, firing rates increased at the transition from NREM to REM (Evarts, 1964;McCarley and Hobson, 1971;Vyazovskiy et al, 2009;Renouard et al, 2015; but also see Niethard et al, 2016). However, similar to the hippocampus, firing rate distributions widened upon this transition, with higher firing neocortical cells showing relatively larger increases at the transition to REM (Δfiring rate = 24.9±5.4%, 33.3±5.7%, 34.0±4.1%, 53.9±6.7%, and 41.3±3.8%, for each quintile from last 1/3 of NREM to first 1/3 of REM, F (4) = 4.3, p = 0.002, one-way ANOVA; Fig.…”
Section: Differential Effects Of Rem and Nrem On Higher-and Lower-firmentioning
confidence: 99%
“…Although these neurons were identified more than 30 years ago, recent studies have demonstrated that most of these neurons contain glutamate, and that some also contain GABA [33;34]. Supramammillary neurons that project to the dentate gyrus of the hippocampus may release both neurotransmitters, and are thought to be active during REM sleep [34]. However, the cortically projecting neurons are mainly just glutamatergic, and chemogenetic activation of them strongly promotes waking [35].…”
Section: Supramammillary Glutamatergic and Gabaergic Arousal Systemmentioning
confidence: 99%